WHO DID ENRICH FASTEST? A COMPARISON OF THE ECONOMIC GROWTH OF BALTIC COUNTRIES IN 1913–1938 - Norkus, Zenonas (Politologija, 2015)
The paper compares the economic growth of Estonia, Latvia, Lithuania, and Finland (which was internationally perceived as a Baltic country in the interwar time) in 1913–1938. The maddison project dataset is a standard (and only available) source providing comparable data (in 1990 Geary–Khamis international $) on the GDP of European countries in the 1913–1938. However, its present version provides only the data about Finland’s performance. The Estonian historian Jaak Valge calculated internationally and cross-temporarly comparable Estonian GDP figures for the 1923– 1938 period. Applying a similar (“Estonian”) procedure of indirect measurement, the paper provides the estimates of the GDP per capita of Latvia and Lithuania in 1913, 1924, and 1938. The data inputs for these estimates are the calculations of national income (in current prices) by Latvian, Lithuanian, and German (The Economic Forces of the World, 1929) economists in the interwar time, the calculations of Kazimieras Meškauskas of the national income of Lithuania (at constant prices of 1924), and (most importantly) the pioneering research on the national income at purchasing power parity by Colin Clark (1905–1989). For the estimation of the national income of Latvia in 1913–1938, the author draws on the Clark’s calculations of Latvia’s national income from the second edition of his “Conditions of Economic Progress” (1951), which until now were not received in the interwar Latvia economic history. Taking into account the recent work of the leading Lithuanian expert in the interwar economic history Gediminas Vaskela, the author revises his estimates of the GDP Lithuania, published in the monograph “Two Twenty-Year Periods of Independence: Capitalism, Class, and Democracy in the First and Second Republics of Lithuania from the Point of View of Comparative Historical Sociology” (2014). Although in 1938 Lithuania still was the least advanced Baltic country, its GDP per capita average yearly growth rate (4.3%) in 1924–1938 was the fastest. Finland’s GDP per capita yearly growth rate was 3.5%, Latvia’s 3.2%, and Estonia’s 1.9%.